2017
DOI: 10.1093/annonc/mdw442
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomic analysis of HER2 expression in the selection of gastric cancer patients for trastuzumab treatment

Abstract: BackgroundA wide range of response rates have been reported in HER2-positive gastric cancer (GC) patients treated with trastuzumab. Other HER2-targeted therapies for GC have yet to show efficacy in clinical trials. These findings raise question about the ability of standard HER2 diagnostics to accurately distinguish between GC patients who would and would not benefit from anti-HER2 therapies.Patients and methodsGC patients (n = 237), including a subset from the Trastuzumab in GC (ToGA) trial were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 19 publications
3
42
0
Order By: Relevance
“…26,37,38 In summary, MET FISH and Met SRM were independently associated with a poor prognosis in this large cohort of GEC patients, whereas Met IHC at the currently applied positivity cutoffs was not independently associated with outcomes. SRM is a novel technology demonstrating clinical utility with Met and Her2 11,27,39,45 and additionally has the advantage of multiplex peptide analysis, 22 which is analogous to nextgeneration sequencing for genomic aberrations. The results of this study suggest that amplification by FISH and/or overexpression by SRM should be incorporated into multivariate models when one is assessing the prognostic significance of other novel covariates.…”
Section: Discussionmentioning
confidence: 99%
“…26,37,38 In summary, MET FISH and Met SRM were independently associated with a poor prognosis in this large cohort of GEC patients, whereas Met IHC at the currently applied positivity cutoffs was not independently associated with outcomes. SRM is a novel technology demonstrating clinical utility with Met and Her2 11,27,39,45 and additionally has the advantage of multiplex peptide analysis, 22 which is analogous to nextgeneration sequencing for genomic aberrations. The results of this study suggest that amplification by FISH and/or overexpression by SRM should be incorporated into multivariate models when one is assessing the prognostic significance of other novel covariates.…”
Section: Discussionmentioning
confidence: 99%
“…23 This dichotomous approach inevitably leaves some patients in the gray area (equivocal) and some have discordant results of these 2 assays. 25,26 Both of our exceptional responders had high levels of HER2 protein in their tumors measured by a clinical quantitative proteomics assay, demonstrating a potential as an alternative assay in predicting the benefit of HER2 therapy, which could be replacing or complementing current methods. Previous research has shown that FIGURE 3 Human epidermal growth factor receptor-2 (HER2) expression level in salivary duct carcinomas using clinical proteomics.…”
Section: Figurementioning
confidence: 93%
“…Previous research has shown that FIGURE 3 Human epidermal growth factor receptor-2 (HER2) expression level in salivary duct carcinomas using clinical proteomics. 24,25 Although proteomic expression of HER2 in the nonresponder is above these cutoffs, it is at the low end of the range of expression correlated with benefit. 18 The HER2 expression level in tumors are calculated from the ratio of area under the curve for the endogenous transition ions for HER2 peptide A, C, and E, and isotopically labeled internal standard peptide B, D, and F, multiplied by the known amount of standard peptides spiked into the samples.…”
Section: Figurementioning
confidence: 99%
“…Furthermore, many patients have tumors that are not strongly positive for ErbB2. In breast cancers and gastric cancers, level of Erb2 measured by quantitative proteomic assay was shown to correlate with response to Erb2 targeting therapy [77, 78]. Further investigations are needed to clarify whether Erb2 level can serve as a predictive biomarker.…”
Section: Systemic Therapies For Sdcmentioning
confidence: 99%